Growth Rate of Beef Cattle to Supporting Livestock Agribusiness in South Sulawesi - Astati, Astati; Hifizah, Amriana; Qurniawan, Anas (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
Developing beef cattle in Indonesia has great potential to meet the demand for beef, improve farmers' welfare, and positively contribute to the national economy. This study aims to identify development areas and analyze the growth rate of beef cattle in South Sulawesi Province. The sampling of areas was done purposively. The data analysis includes the Location Quotient (LQ) and the Growth Ratio Model (GRM). The study results indicate that Bulukumba, Sinjai, Maros, Bone, Barru, Wajo, and Enrekang Regencies are the leading (base) areas for beef cattle development in South Sulawesi Province. The growth rate of beef cattle that falls into classification I includes Selayar Islands, Bulukumba, Takalar, Gowa, Sinjai, Bone, Wajo, Pinrang, Tana Toraja, North Luwu, and East Luwu Regencies. Meanwhile, Bantaeng, Jeneponto, Maros, Pangkajene and Islands, Barru, Soppeng, Enrekang, and Luwu Regencies, as well as the cities of Makassar, Parepare, and Palopo, are included in classification II. This information on the growth rate of beef cattle serves as a basis for local governments to determine appropriate policies for sustainable beef cattle development in these areas. The growth of beef cattle to support livestock agribusiness can be achieved through the development of digital-based technology. This can significantly contribute to developing livestock agribusiness that is more efficient, sustainable, and profitable